Hubungan Riwayat Sectio Caesarea dengan VBAC (Vaginal Birth After Caesarean) di Klinik Bersalin Hj. Rismala S Kisaran - Nani Jahriani (Journal of Health Science and Physiotherapy, 2019)
VBAC is the promotion of vaginal delivery in women who have undergone a previous caesarean section. About 75% of mothers have had caesarean section at the next labor. At the Maternity Clinic Hj. Rismala. S The range of events in the history of cesarean section with VBAC was 30 people from 335 normal deliveries.To find out the relationship between sectio caesarea and VBAC at the Maternity Clinic Hj. Rismala. S Kisaran in 2018, The study was conducted using a cross-sectional research method with Chi Squer test with a total sample of 30 mothers conducted in July 2018. From the results of the study of 30 samples, it was found that there was no relationship between Age and VBAC both from the age group at risk of 51.9% and the age group who were not at risk 41.9% with OR (0.464). And there is no relationship between parity and VBAC, where mothers with multiparous partasas in the successful group have 50% while in the unsuccessful group 50% with OR (1,000).With the conclusion that there is no relationship between age and VBAC and there is no relationship between parity and VBAC based on data obtained from the Hj Maternity Clinic medical record. Rismala. S Kisaran June 2017-June 2018. That results obtained according to age and parity are not the main considerations because there are other factors that need to be known but not examined by researchers such as uterine incision type, history of rupture, number of previous caesarean deliveries, indications of uterus and complication at the time of delivery which makes the midwife have to make a reference for Sectio Caesarea at the hospital.